2021
DOI: 10.3390/foods11010065
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Caseinate and Acetylated Mung Bean Starch for the Encapsulation of Lutein: Enhanced Solubility and Stability of Lutein

Abstract: Lutein is a kind of vital carotenoid with high safety and significant advantages in biological functions. However, poor water solubility and stability of lutein have limited its application. This study selected different weight ratios of sodium caseinate to acetylated mung bean starch (10:0, 9:1, 7:3, 5:5, 3:7, 1:9, and 0:10) to prepare lutein emulsions, and the microcapsules were produced by spray drying technology. The microstructure, physicochemical properties, and storage stability of microcapsules were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In this study, sample D had the highest EE result and sample C had the lowest EE (Table 2 ). The yak butter EE results were consistent with the findings of Lu et al 13 and Zhang et al 9 , as the authors reported an EE range of 69.72–94.30% in oils encapsulated with NaCas and MD formulations. However, Böger et al 22 reported lower EE (63.47%) in grape seed oil encapsulated with gum arabic and MD formulation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, sample D had the highest EE result and sample C had the lowest EE (Table 2 ). The yak butter EE results were consistent with the findings of Lu et al 13 and Zhang et al 9 , as the authors reported an EE range of 69.72–94.30% in oils encapsulated with NaCas and MD formulations. However, Böger et al 22 reported lower EE (63.47%) in grape seed oil encapsulated with gum arabic and MD formulation.…”
Section: Resultssupporting
confidence: 90%
“…For instance, low viscosities of maltodextrin (MD) and lactose (Lac) complement NaCas’ viscosity to achieve higher encapsulation efficiency (EE) when combined. Conversely, other authors have achieved ideal microcapsule features with only one encapsulation material 12 , 13 . Previous studies combined NaCas with lactose and maltodextrin and reported high EE, oxidative stability, and favorable microcapsule physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the moisture content and wettability The moisture content of microcapsule samples was determined as described by Lu et al (2021) using the vacuum oven drying method. For wettability measurement, microcapsule powder (0.1 g) was added to 50 mL of distilled water at room temperature, stirred on a magnetic stirrer at 450 rpm until the powder was completely immersed.…”
Section: Determination Of Encapsulation Efficiencymentioning
confidence: 99%
“…Esterified acetic starch has good hydrophobic, thermal and emulsification properties (Katerinopoulou et al ., 2014). Therefore, it can be utilised as an emulsifier, stabiliser and fat substitute in the food industry (Lu et al ., 2021). We speculated that a combination of sodium caseinate and esterified starch acetate would have the necessary solubility and emulsification to enhance the performance of single‐wall material.…”
Section: Introductionmentioning
confidence: 99%
“…Yue Pu et al 47 prepared low-temperature phase change microcapsules with a water core and ethyl cellulose wall by the solvent diffusion method. Besides, there are some studies, [48][49][50][51] in which volatile or non-recyclable solvents are used in varying degrees in the preparation of microcapsules, which leads to solvent pollution or resource waste to a certain extent.…”
Section: Introductionmentioning
confidence: 99%